Psychological structure of alexithymic space in patients with cardiovascular diseases - E. Yu. Brel’; N. A. Bokhan; I. Ya. Stoyanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Te paper reports on the features of alexithymic space structure in patients with cardiovascular diseases, comparison of the obtained results with the group of healthy respondents. Tis information is useful for health psychologists to develop models of clinical-psychological support of patients of this category.